Effects of perceived justice for coaches on athletes' trust, commitment, and perceived performance: A study of futsal and volleyball players - Nikbin, D.; Hyun, S. S.; Iranmanesh. M.; Foroughi. B. (International Journal of Sports Science and Coaching, 2014)
This study examines the effects of perceived justice for coaches on athletes' commitment, trust, and perceived performance. A total of 161 futsal and volleyball players in Iran responded to scales measuring three dimensions of perceived justice, namely distributive justice, procedural justice, and interactional justice; commitment; trust; and two dimensions of perceived performance, namely individual performance and team performance. The data were analyzed using the partial least squares method. The results of the confirmatory factor analysis provide support for the measurement model. As expected, all three dimensions of perceived justice were positively and significantly related to commitment and trust. In addition, commitment was significantly related to individual performance and team performance. Further, there was a positive relationship between trust and the three dimensions of perceived performance. The results have important theoretical and practical implications.